Plot size and sustainable input intensification in smallholder irrigated agriculture: Evidence from Egypt - Abay, Kibrom A.; Abdelfattah, Lina Alaaeldin; El-Enbaby, Hoda; Mahmoud, Mai; Breisinger, Clemens (Wiley, 2022)
Increasing population pressure and population density in many African countries are inducing land scarcity and land constraints. Tightening land constraints are expected to trigger various responses, including agricultural intensification, as postulated by the Boserup hypothesis. The relevance of the Boserup hypothesis in irrigated agriculture, and in contexts where application of improved inputs is high, remains largely unexplored. Furthermore, while much of the debate on the topic in Africa has focused on how to boost agricultural intensification, there is scant evidence on whether evolving agricultural intensification practices in some parts of Africa are sustainable. In this article, we investigate the implication of land size (at the plot and farm level) on agricultural intensification. Our analysis sheds light on the relevance of the Boserup hypothesis in the context of Egypt, where irrigation dominates agriculture and input application rates are high relative to global standards. We also examine whether evolving agricultural intensification practices induced by land scarcity are agronomically appropriate. Our findings show that smaller plot and farm sizes are associated with higher application of agricultural inputs, mainly nitrogen fertilizers. Importantly, small plot size is associated with overapplication of nitrogen fertilizer relative to crop-specific agronomic recommendations. In addition, smaller plots are associated with higher rates of labor application and lower rates of mechanization.